KONTRIBUSI POWER OTOT TUNGKAI DAN REAKSI TERHADAP TENDANGAN T ATLET CLUB SILAT PLAY BANDAR LAMPUNG - Zaa'idah, Salma; Surisman; Sumantri , Riyan Jaya; Wicaksono, Lungit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the contribution of leg muscle power and reaction to the T kick of Bandar Lampung athletes. The method used is a descriptive correlational method. The research sample consisted of 40 people. The research instruments used were leg muscle power tests using Vertical Jump, reaction tests using Wall Body Reaction, T kick tests using hand back targets. Research hypotheses: 1) there is a contribution of leg muscle power to the T kick, 2) there is a contribution of reaction to the results of the T kick, 3) there is a contribution of leg muscle power and reaction to the T kick. The results of the study showed that: 1) there is a significant contribution between leg muscle power to the T kick (r count = 0.559 > r table = 0.374), 2) there is a significant contribution between reaction to the T kick (r count = 0.481 > r table = 0.374), 3) Simultaneously, the contribution of leg muscle power and reaction to the T kick (r count = 0.562 > r table = 0.374) and a contribution of 31.65%.